2016
DOI: 10.1111/acel.12547
|View full text |Cite
|
Sign up to set email alerts
|

Familial longevity is characterized by high circadian rhythmicity of serum cholesterol in healthy elderly individuals

Abstract: SummaryThe biological clock, whose function deteriorates with increasing age, determines bodily circadian (i.e. 24h) rhythms, including that of cholesterol metabolism. Dampening of circadian rhythms has been associated with aging and disease. Therefore, we hypothesized that individuals with a familial predisposition for longevity have a higher amplitude circadian serum cholesterol concentration rhythm. The aim of this study was to investigate circadian rhythmicity of serum cholesterol concentrations in offspri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Participants were allowed to sleep from 2300 hr to 0800 hr, during which lights were off, and consumed identical standard liquid test meals at clock times 0900, 1200, and 1800 hr. TG levels of this cohort were reported before and were found to be rhythmic (van den Berg et al, 2017). Postprandial AUCs at 9-12 hr (3.2 ± 0.2 mM , hr) were lower compared to 12-15 hr (5.0 ± 0.3 mM , hr; p < 0.0001) and 18-21 hr (4.0 ± 0.2 mM , hr; p < 0.001) ( Figure S4).…”
Section: Postprandial Lipid Response In Humans Is Dependent On the Tisupporting
confidence: 68%
See 1 more Smart Citation
“…Participants were allowed to sleep from 2300 hr to 0800 hr, during which lights were off, and consumed identical standard liquid test meals at clock times 0900, 1200, and 1800 hr. TG levels of this cohort were reported before and were found to be rhythmic (van den Berg et al, 2017). Postprandial AUCs at 9-12 hr (3.2 ± 0.2 mM , hr) were lower compared to 12-15 hr (5.0 ± 0.3 mM , hr; p < 0.0001) and 18-21 hr (4.0 ± 0.2 mM , hr; p < 0.001) ( Figure S4).…”
Section: Postprandial Lipid Response In Humans Is Dependent On the Tisupporting
confidence: 68%
“…In rodents, plasma TG and FA levels show diurnal variations reaching their lowest levels at the start of the dark, active period (Pan et al, 2010;Rudic et al, 2004;Shostak et al, 2013). We (van den Berg et al, 2017) and others (Chua et al, 2013) have shown that, also in humans, plasma lipid concentrations vary over the day, which could only partly be explained by food intake, suggesting a contribution of oscillations in the clearance of lipids by metabolic organs. We hypothesized that BAT contributes to the diurnal regulation of plasma lipids.…”
Section: Introductionmentioning
confidence: 56%
“…Their results are consistent with the present study; however, they did not evaluate a rhythmic component via the Fourier transform method. Significant daily variations in the HDL-C levels were detected by Rivera-Coll et al ( 48 ) and Van den Berg et al ( 49 ). However, Van Den Berg et al ( 49 ) did not evaluate a rhythmic component.…”
Section: Discussionmentioning
confidence: 90%
“…Significant daily variations in the HDL-C levels were detected by Rivera-Coll et al ( 48 ) and Van den Berg et al ( 49 ). However, Van Den Berg et al ( 49 ) did not evaluate a rhythmic component. Notably, different analytical methods in other studies make it difficult to compare the result that lack of circadian rhythm associated with HDL-C levels in the present study; a fact that may explain, in part, the observed differences in timing and daily amplitude between the present research and other studies.…”
Section: Discussionmentioning
confidence: 90%
“…We investigated SNP-sleep interactions in a large, multi-ancestry, meta-analysis of blood lipid levels. Given the growing evidence that sleep influences metabolism [39][40][41][42][43][44] HDL-c (1.00% and 0.97%) was low/modest, the novel lead SNPs identified include genes known to be associated with adiposity, inflammatory disorders, cognition, and liver function, thus identifying pathways by which sleep disturbances may influence lipid biology.…”
Section: Discussionmentioning
confidence: 99%